A113 LINKING GENE-ENVIRONMENT INTERACTIONS IN IBD: VITAMIN D-MEDIATED REGULATION OF AUTOPHAGY. (1st March 2018) - McGillis, L H; Johnson, S; Bronte-Tinkew, D; Dang, F; Philpott, D; Jones, N
Abstract: Background: The incidence of IBD has risen dramatically over the past decade, indicating a role for environmental factors in disease onset. Growing evidence from animal and human studies indicate that vitamin D deficiency is an important environmental factor contributing to IBD pathogenesis, although the exact mechanism involved remains unknown. Autophagy is a pathway that has gained interest for its recently established role in IBD pathogenesis. Previously in our lab, we have shown that inducing vitamin D deficiency in wildtype C57Bl/6 mice causes a significant downregulation of autophagy proteins ATG16L1 and LC3II in the intestine. Aims: We aim to elucidate the relationship between vitamin D deficiency and IBD by exploring the effect of vitamin D on intestinal autophagy. We hypothesize that vitamin D deficiency plays a role in the dysregulation of autophagy in the intestine. Methods: To complement our previous findings and to directly assess the effect of vitamin D on intestinal epithelial cells and autophagy, we employed in vitro experiments using murine intestinal epithelial (MODE-K) cells and murine intestinal organoids. Cells were incubated with increasing concentrations of the active form of vitamin D. Western blotting was performed to evaluate autophagy markers ATG16L1 and LC3II, as well as the vitamin D receptor (VDR), a vitamin D responsive gene. Results: As expected, a significant and dose-dependent increase in VDR expression was detected in cells incubated with vitamin D. Furthermore, a trend towards increased ATG16L1 was detected in vitamin D treated cells. Conclusions: Our findings suggest that vitamin D upregulates the autophagy protein ATG16L1 providing a potential mechanism by which vitamin D deficiency modulates IBD pathogenesis. Given this interesting interaction between vitamin D and autophagy, the next step of this project is to assess the effect of vitamin D deficiency in the context of IBD susceptibility Nod2 mutations. Funding Agencies: CCCOGS, Restracomp